(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This article analyzes the study of optical, magneto-optical properties of rare earth ions. The velocity of ion movement, the magnetic optics of radiant 4f-4f transitions in garnets of rare earth elements are described in detail. The results of the research can be widely applied in the field of quantum electronics, optoelectronics, microelectronics, physical physics optics.